Historical and elevational contamination by toxic metals and arsenic in hummingbirds in southeastern Mexico: a variable to consider in the face of the global pollinator crisis - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina Esperanza Rodríguez-Yah; Jaime Rendón-von Osten (Environmental Research, 2026)

Temporal trends (1937–2006) in concentrations of toxic elements in neotropical birds from southeastern Mexico - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina Esperanza Rodríguez-Yah; Jaime Rendón-von Osten (Environmental Monitoring and Assessment, 2026)

Neural Correlates of Inhibitory Control in Children: Evidence Using MRI and fNIRS - Leela Shah; Xin Zhou; Marissa Ann DiPiero; Jayse Merle Weaver; Corrina Frye; Steven R. Kecskemeti; Ruth Y. Litovsky; Andrew L. Alexander; Elizabeth M. Planalp; Douglas C. Dean (Brain Topography, 2025)
Inhibitory control (IC) develops in stages from infancy through adolescence and is associated with numerous developmental disorders and learning outcomes. This study examined how neural architecture – in particular myelination – underlies brain activation patterns observed during IC tasks in a sample of 28 children aged 4–10 years old. IC was observed using reaction times during go/no-go and flanker IC tasks. Myelination was measured using quantitative longitudinal relaxation rate (R1) mapping obtained from selected white matter regions of interest (ROIs). Brain activation was defined as task-related changes in hemoglobin oxygenation as measured by functional near-infrared spectroscopy (fNIRS) averaged within ROIs. Results indicated that myelination in ROIs was higher in older children and fNIRS activation in frontal channels was significantly and positively associated with go/no-go mean reaction time. Myelination in the corona radiata and superior longitudinal fasciculus was positively associated with frontal fNIRS activation, while myelination was negatively associated with go/no-go and flanker mean reaction times across white matter ROIs. Overall, significance level notably varied across models. Independently of inhibitory control constructs, these regions may be of interest in future structure-function studies across development.

Interaction of non-biodegradable particles and granular sludge in Nereda®—— from nanoparticles to microparticles - Zhaoxu Peng; Antonella L. Piaggio; Guilherme Lelis Giglio; Sara Toja Ortega; Mark C.M. van Loosdrecht; Merle K. de Kreuk (Water Research, 2025)

Historical (1960 – 2011) and spatial analysis of mercury and arsenic in two species of tropical birds in southeastern Mexico - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina E. Rodríguez-Yah; Jaime Rendón-von Osten (Journal of Hazardous Materials, 2025)

Detecting the interaction between microparticles and biomass in biological wastewater treatment process with Deep Learning method - Tianlong Jia; Zhaoxu Peng; Jing Yu; Antonella L. Piaggio; Shuo Zhang; Merle K. de Kreuk (Science of The Total Environment, 2024)

Synergistic effects of microplastic and lead trigger physiological and biochemical impairment in a mangrove crab - Mariana V. Capparelli; Ricardo Dzul-Caamal; Erick M. Rodríguez-Cab; Merle M. Borges-Ramírez; Jaime Rendón-von Osten; Karen Beltran; Brian Pichardo-Casales; Alethia I. Ramírez-Olivares; Jorge Arturo Vargas-Abúndez; Carl L. Thurman; Gabriel M. Moulatlet; Carlos Rosas (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Iron Oxide Nanoparticles Induce Dopaminergic Damage: In vitro Pathways and In Vivo Imaging Reveals Mechanism of Neuronal Damage - Syed Z. Imam; Susan M. Lantz-McPeak; Elvis Cuevas; Hector Rosas-Hernandez; Serguei Liachenko; Yongbin Zhang; Sumit Sarkar; Jaivijay Ramu; Bonnie L. Robinson; Yvonne Jones; Bobby Gough; Merle G. Paule; et al. (Molecular Neurobiology, 2015)

Reducing greenhouse gas emissions, water use, and grain arsenic levels in rice systems - Bruce A. Linquist; Merle M. Anders; Maria Arlene A. Adviento‐Borbe; Rufus L. Chaney; L. Lanier Nalley; Eliete F.F. da Rosa; Chris van Kessel (Global Change Biology, 2015)
Agriculture is faced with the challenge of providing healthy food for a growing population at minimal environmental cost. Rice ( Oryza sativa ), the staple crop for the largest number of people on earth, is grown under flooded soil conditions and uses more water and has higher greenhouse gas ( GHG ) emissions than most crops. The objective of this study was to test the hypothesis that alternate wetting and drying ( AWD – flooding the soil and then allowing to dry down before being reflooded) water management practices will maintain grain yields and concurrently reduce water use, greenhouse gas emissions and arsenic (As) levels in rice. Various treatments ranging in frequency and duration of AWD practices were evaluated at three locations over 2 years. Relative to the flooded control treatment and depending on the AWD treatment, yields were reduced by GWP of CH 4 and N 2 O emissions) reduced by 45–90%, and grain As concentrations reduced by up to 64%. In general, as the severity of AWD increased by allowing the soil to dry out more between flood events, yields declined while the other benefits increased. The reduction in GWP was mostly attributed to a reduction in CH 4 emissions as changes in N 2 O emissions were minimal among treatments. When AWD was practiced early in the growing season followed by flooding for remainder of season, similar yields as the flooded control were obtained but reduced water use (18%), GWP (45%) and yield‐scaled GWP (45%); although grain As concentrations were similar or higher. This highlights that multiple environmental benefits can be realized without sacrificing yield but there may be trade‐offs to consider. Importantly, adoption of these practices will require that they are economically attractive and can be adapted to field scales.

Diatom-inferred late Pleistocene and Holocene palaeolimnological changes in the Ioannina basin, northwest Greece - Timothy D. Jones; Ian T. Lawson; Jane M. Reed; Graham P. Wilson; Melanie J. Leng; Merle Gierga; Stefano M. Bernasconi; Rienk H. Smittenberg; Irka Hajdas; Charlotte L. Bryant; P. C. Tzedakis (Journal of Paleolimnology, 2013)

Potentially inappropriate drug prescription in the elderly in France: a population-based study from the French National Insurance Healthcare system - B. Bongue; M. L. Laroche; S. Gutton; A. Colvez; R. Guéguen; J. J. Moulin; L. Merle (European Journal of Clinical Pharmacology, 2011)

Bayesian pharmacokinetic estimation of vinorelbine in non-small-cell lung cancer patients - C. Sabot; P. Marquet; J. Debord; N. Carpentier; L. Merle; G. Lachâtre (European Journal of Clinical Pharmacology, 1998)

Minutes of section’ meetings - Gary A. Secor; David Holm; Oscar Gutbrod; Dermot Lynch; Joseph B. Sieczka; Merle L. Weaver (American Journal of Potato Research, 1983)

Changes in nutritional composition of Russet Burbank potatoes by different processing methods - Merle L. Weaver; Herman Timm; Hawkins Ng (American Journal of Potato Research, 1983)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Leaching of french-fried potato strips - Merle L. Weaver; E. Hautala (American Journal of Potato Research, 1971)

Interaction of 2,4-D maleic hydrazide, and minor element uptake in potatoes - E. Merle Harrison; Jess L. Fults; Merle G. Payne (American Journal of Potato Research, 1958)

Detection of potato leaf roll by paper chromatography and electrophoresis - Charles W. McAnelly; Merle G. Payne; Jess L. Fults (American Journal of Potato Research, 1956)

The effect of 2,4-D and maleic hydrazide on sprouting, yields and color in red McClure potatoes - Jess L. Fults; Merle G. Payne (American Journal of Potato Research, 1955)

The effect of maleic hydrazide and 2,4-D on reducing sugars and sucrose of Red McClure potatoes - Merle G. Payne; Jess L. Fults (American Journal of Potato Research, 1955)

Protein content and specific gravity of Red McClure potatoes increased by 2,4-D treatment - Merle G. Payne; Jess L. Fults; Ruth J. Hay; Clark H. Livingston (American Journal of Potato Research, 1953)

The effect of 2,4-d treatment on free amino acids in potato tubers - Merle G. Payne; Jess L. Fults; Ruth J. Hay (American Journal of Potato Research, 1952)

Nitrate content of red mcclure potatoes unchanged by 2,4-d treatment - Jess L. Fults; Ruth J. Hay; Merle G. Payne (American Journal of Potato Research, 1952)

The effect of storage on color and sprouting of Red McClure potatoes after 2,4-D treatment - Merle G. Payne; Jess L. Fults; Ruth Hay; Nellie Landblom; L. A. Schaal (American Journal of Potato Research, 1951)

Stabilization and intensification of red skin color in Red McClure potatoes by use of the sodium salt of 2,4-dichloro-phenoxyacetic acid - Jess L. Fults; L. A. Schaal; Nellie Landblom; Merle G. Payne (American Journal of Potato Research, 1950)